2013
DOI: 10.1007/s00220-013-1715-0
|View full text |Cite
|
Sign up to set email alerts
|

Ergodic Properties of Random Billiards Driven by Thermostats

Abstract: Abstract:We consider a class of mechanical particle systems interacting with thermostats. Particles move freely between collisions with disk-shaped thermostats arranged periodically on the torus. Upon collision, an energy exchange occurs, in which a particle exchanges its tangential component of the velocity for a randomly drawn one from the Gaussian distribution with the variance proportional to the temperature of the thermostat. In the case when all temperatures are equal one can write an explicit formula fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…Non-equilibrium steady states for open mechanical particle systems have been extensively studied in recent years as a part of the efforts to derive the Fourier Law from the laws of microscopic dynamics [1, 3, 5, 7, 11-13, 15, 18]. The existence of non-equilibrium steady states has been rigorously shown for only a handful of systems, mostly by using either spectraltheoretic arguments [4,6,8] or Harris' ergodic theorem [12,17]; these methods automatically yield exponential mixing and exponential rates of convergence of initial distributions to the unique steady state. For systems that do not mix exponentially fast, which is frequently the case for continuous-time mechanical particle systems driven by heat reservoirs, general methods to prove the existence of non-equilibrium steady states are virtually non-existent.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-equilibrium steady states for open mechanical particle systems have been extensively studied in recent years as a part of the efforts to derive the Fourier Law from the laws of microscopic dynamics [1, 3, 5, 7, 11-13, 15, 18]. The existence of non-equilibrium steady states has been rigorously shown for only a handful of systems, mostly by using either spectraltheoretic arguments [4,6,8] or Harris' ergodic theorem [12,17]; these methods automatically yield exponential mixing and exponential rates of convergence of initial distributions to the unique steady state. For systems that do not mix exponentially fast, which is frequently the case for continuous-time mechanical particle systems driven by heat reservoirs, general methods to prove the existence of non-equilibrium steady states are virtually non-existent.…”
Section: Introductionmentioning
confidence: 99%
“…An excellent review of the ideas and difficulties associated with this task is presented in [9]. This paper, together with [12], provides a rigorous proof of the existence of a unique steady state with sub-exponential mixing rates for a class of random billiards driven by thermostats which randomize the velocities only in one direction, leaving a large memory trace in the system. In addition, for a large class of initial distributions, we obtain polynomial lower bounds on the rates of convergence to the steady state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [5], it is shown that the Maxwell-Boltzmann distribution is the equilibrium distribution for a large class of examples with a single heat bath. Ergodicity was proved for reflection models with multiple temperatures in [18], but this is for a special class of billiard tables, using the geometry of dispersing Sinai billiards.…”
mentioning
confidence: 99%
“…In this paper, we consider a class of particle systems for which such modeling is more straightforward, namely when the particles do not interact with one another directly but only via their "environment", or a "hub". Concrete examples of mechanical models of this type were introduced in [33,36] and studied later in [10,30,29,11,12,13,44,25]. In these models, the "environment" is symbolized by the kinetic energy stored in rotating disks placed at various locations in the physical domain.…”
mentioning
confidence: 99%